Population Analysis of Bali Sardinella (Sardinella lemuru, Bleeker 1853) Landed in PPI Kedonganan using Length-Weight Data and Digital Analysis (ImageJ) - Ni Putu Dian Pertiwi; Ida Ayu Purnama Bestari; M. Danie Al Malik; Mark Anthony Phuong (Marine Science Department Diponegoro University, 2023)
Sardinella lemuru, one of the important pelagic fish in Bali Strait waters, has been reported to be in the overfishing condition. Various studies have been conducted to understand its population condition. Length-weight data has been also widely used to understand the population dynamic of S. lemuru, although data collection generally using manual direct measurement methods, which has the disadvantages if used on the enormous number of samples. Therefore, this research aims to understand the significance of S. lemuru length measurement using digital image analysis (ImageJ) compared with the manual measurement. Moreover, this research also aims to understand the population condition of S. lemuru landed in PPI Kedonganan analyzed using its length-weight data. The result indicated no significance difference between length measurement using manual methods and digital image methods, thus conclude that digital image data can be used to measure the fish length and represent the accurate measurement. Population condition analysis showed that S. lemuru population is in isometric condition (b=3); with indication of declining in the length growth pattern compared with previous research (L∞= 20.75 cm with K= 1.1); the mortality estimation showed that fishing mortality (F=1.27) was lower than natural mortality (M=2.22), with the survival rate higher on smaller size fish. This research result can be used as an addition to the S. lemuru fisheries data and can also be used as reference methods to help conduct sampling and data collection more efficiently.